NARRATIVE STRUCTURE OF NE’ BARUAKNG KULUP TALE ORAL LITERATURE OF DAYAK KANAYATN: A STUDY OF ACTANTIAL A.J. GREIMAS - Sesilia Seli; Antonius Totok Priyadi; Sisilya Saman; Laurensius Salem (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura, 2018)
This study is based on the importance of conducting an in-dept study of the characters of Ne’ Baruakng Kulup story of Dayak Kanayatn’s oral literature. This story narrates an attempt made by Baruakng to bring paddy into the earth which was full of obstacles so that he was named Ne’ Baruakng Kulup. The life dynamic of Baruakng is interesting to study more in-depth by using the study of narrative structure based on the thinking of A.J. Greimas. This qualitative study was focused on three important elements, namely: (1) the actantial scheme and functional structure in the story of Ne’ Baruakng Kulup; (2) the correlation between the actantial scheme and the functional structure in the story of Ne’ Baruakng Kulup; and (3) Compiling a lecture plan of the Prose Study by applying the results of Actantial study on the story of Ne’ Baruakng Kulup. The results of this study indicate that there are 14 actantial schemes and 14 functional structures. Four actant schemes and 4 perfect functional structures and 10 actant schemes, and 10 imperfect functional structures. The main actant scheme lies in scheme 6. There a correlationrelationship between the actant scheme and the functional structure. The character of Ne’ Baruakng Kulup is a hero in the story analyzed. In accordance with this, a Semester Lecture Plan has been designed for Prose Study by implementing an actantial analysis based on A.J. Greimas on the tale of Ne’ Baruakng Kulup in practicing analyzing folklore.